Convective boiling of R-134a and R-123 on an enhanced tube bundle with standard pitch, RP-1316 - Gorgy, Evraam; Eckels, Steven J. (My University, 2013)
The current paper presents the experimental investigation of the heat transfer performance of highly enhanced surfaced tube bundles. The two bundles studied are high pressure and low pressure TBII tubes for R-134a and R-123, respectively. The tube bundle is a staggered triangular arrangement with a tube pitch of (P/D 1.167). Twenty enhanced tubes were used in the bundle; the tube outer diameter and length are 19.05 mm (3/4 inch) and 1 m (39.36 inch), respectively. Three input variables were studied: heat flux (5-60 kW/m²), mass flux (15-55 kg/m².s), and quality (10-70%). The test saturation temperature was 4.44 °C for R-134a and 14.44 °C for R-123. The local heat transfer performance of the bundle is reported. A local method employing the Enthalpy Based Heat Transfer technique was implemented in the data reduction. Both tube bundles showed a strong dependency on heat flux as expected. The R-134a bundle showed a performance lower than that of pool boiling. The R-123 bundle showed a secondary dependency on quality. The quality effect becomes pronounced at high qualities and high average bundle heat load. In latter case enhanced tubes performance drops quickly and reaches that of a smooth tube.
Keywords: Tube bundles; Heat transfer; Heat flux